Hubungan Efikasi Diri dan Tingkat Stres dengan Manajemen Perawatan Diri pada Pasien Diabetes Mellitus Tipe 2 - Titis Nurhandayani; Retno Setyawati; Erna Melastuti (CV SCRIPTA INTELEKTUAL MANDIRI, 2025)
Type 2 diabetes mellitus is a chronic condition that requires continuous self-care management to prevent complications and maintain glycemic control. However, self-care performance is not solely determined by physical factors, but also influenced by psychological aspects, particularly self-efficacy and stress level. This study aimed to analyze the relationship between self-efficacy and stress level with self-care management among patients with type 2 diabetes mellitus. A quantitative cross-sectional design was applied at Guntur 1 Public Health Center from September 16 to October 14, 2025. The study involved 120 patients selected using total sampling. Data were collected using structured questionnaires, including the Diabetes Management Self-Efficacy Scale (DMSES), Perceived Stress Scale (PSS-10), and Diabetes Self-Management Questionnaire (DSMQ). Data analysis was conducted using Gamma correlation with a significance level of p < 0.05. The results indicated a significant relationship between self-efficacy and self-care management (p = 0.006; r = 0.576). Stress level also showed a significant and strong relationship with self-care management (p = 0.001; r = 0.725). Strengthening self-efficacy and stress management should be prioritized in nursing interventions to support sustainable diabetes self-care behaviors.